A rapid and systemic complete response to stereotactic body radiation therapy and pembrolizumab in a patient with metastatic renal cell carcinoma. Issue 8 (3rd August 2017) - Xie, Guozhu; Gu, Di; Zhang, Lanfang; Chen, Shijun; Wu, Dehua
ABSTRACT: Stereotactic body radiation therapy (SBRT) of local tumor would induce an abscopal effect that has been observed in several kinds of human cancers; one important mechanism may involve the improved activation of the host immune system. The immune checkpoint inhibitor can overcome immune tolerance and enhance the activation of antitumor T cells. The combined treatment of SBRT and checkpoint inhibitor may represent a new promising therapeutic approach. Herein, we reported a patient with metastatic renal cell carcinoma (RCC) treated with concurrent SBRT and anti-PD-1 antibody, pembrolizumab, by which the patient achieved an amazingly systemic complete response in only 2.2 months after starting treatment. This case report indicates that the advanced RCC may benefit from the combining treatment of local SBRT and PD-1 inhibitor and provide a useful paradigm worthy of establishing a clinical trial for patients with advanced renal cell carcinoma.